PENERAPAN MEDIA SCRAP POP BOOK UNTUK PENINGKATAN HASIL BELAJAR PADA MATERI KEMERDEKAAN DAN PERISTIWA DISEKITARNYA - Ina Ilmi Fahima; Widia Nur Jannah; Dewi Yuningsih; Mulyani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Cognitive learning outcomes are measurable and observable changes resulting from learning experiences that align with instructional objectives. Based on IPAS (Integrated Science) test scores, 83% of students scored below the minimum passing grade (KKM). This research aimed to enhance the cognitive learning outcomes in IPAS for sixth-grade students at SDN Kemakmuran 2 Cirebon through instructional media. The medium employed was a scrap pop book (Scrap Book and Pop Up), which contains visually presented content. The subjects were 30 sixth- grade students. This classroom action research utilized the Kemmis and McTaggart model. Testing techniques were used to determine the improvement in learning outcomes. In the first cycle, the average learning outcome was 66.6, categorized as 'satisfactory.' This result improved in the second cycle to 82.6, categorized as 'good.' Therefore, it can be concluded that the scrap pop book media effectively enhances students' learning outcomes in the topic of 'Independence and Surrounding